Spatial analysis of Texture and Soil Structure Characteristics and their effect on wheat and barley producation in Ranya District - Bnar Abdulkhaliq Bakir; Ahmed Yassen Ali (Zanco Journal of Humanity Sciences)
The aim of this study is to determine the types of soil in Ranya district and analyze its physical characteristics in terms of texture and soil structure and suitability for planting wheat and barley. Research on soil texture and structure is of great importance in agriculture, so from this perspective we can determine the capacity of the soil to produce crops. During our research, we were able to take 39 soil samples from the study area, which are divided into soil types according to Buring classification using the Geographic Information System (Arc GIS) program. To reach the results of the research, we relied on descriptive and analytical methods. The results of the study showed that there are two types of soil texture in Ranya district, namely clay loam texture and loam texture that are suitable for cultivation of wheat and barley in the study area. It is also clear that the structure spheroid is the best type of soil structure in Ranya district, which is the most common soil samples in the study area. However, blocky structured and structures less are considered to be the worst types of soil structures that are not suitable for agriculture, including wheat and barley cultivation, which are found in certain small areas in the study area.